The Land of the Dead - Osborne, Mary Pope.; Homer; Howell, Troy (New York : Hyperion Books for Children, 2002)
A retelling of part of the Odyssey in which Odysseus and his fleet continue their journey and encounter giant cannibals, a beautiful witch, and the Land of the Dead.
Map on endpapers.
Wilson's Children.
School Library Journal.
Horn Book.
5.0
3-6
Keywords: Odysseus (Greek mythology) -- Fiction; Mythology, Greek; Odysseus (Greek mythology) -- Fiction; Classical mythology -- Fiction; Odysseus -- (Mythological character); Mythology, Greek